La artesanía en la Parroquia Rural San Carlos del cantón Quevedo como atractivo turístico - Vera Soto, Alisson Nahomy (2020)
This research work refers to the crafts in the rural parish San Carlos den Cantón del Quevedo, as a tourist attraction which leads to the development of a proposal to establish proposals for these crafts to be established as a source of economic development for the parish obtaining the implementation of a cultural tourism for the parish, for which a total of one hundred people from the locality. The choice of respondents was taken randomly, considering that the required number of these is in accordance with the formula proposed for the investigation, a theoretical distribution of the different frequencies was developed in order to visibly appreciate, using the graphs of the unlike cakes , the representative values of the sample. The values showed that the handicrafts most people do not have any knowledge of the crafts in San Carlos and that the cultural value of this should be prioritized, since through this one a majority tourist income would be obtained, thus obtaining an increase economic to the parish, thus trying to boost the functioning and knowledge of these works; with the purpose of promoting cultural tourism. It should be emphasized that there is insufficient information on these handicrafts, and the absence of these contributions by the entities in charge of parish cultural development, and through the different strategies a dissemination of these handicrafts can be promoted, thus achieving that cultural tourism achieves promote this knowledge.